Analisis Sektor-Sektor Ekonomi Terhadap Penerimaan Daerah Kabupaten Wajo - Bunaya, Bunaya; Musa, Chalid Imran; Rahmatullah, Rahmatullah (JEKPEND: Jurnal Ekonomi dan Pendidikan, 2019)
This study aims to find out the basic economic sector, strategic economic sectors and the potential to be developed as supporting regional revenues in Wajo District. The study was descriptive quantitative research which employed gross regional domestic product data and rate of economic growth in 2012-2016. The method analysis used Location Quotient (LQ), Shift Share, and Klassen Typology. The results of the study reveal that the base sectors are agriculture, forestry and fishery, mining and excavation, procurement of electricity and gas, large and retail trade, and car and motorcycle repair; whereas, other sectors are included as non-base. The results of shift share method reveal that the competitive sectors are agriculture, forestry and fishery, government administration, mandatory defense and social security, educational services, transportation and warehousing, real estate, financial services, information and communication, health services and social activities, other services, provision of accommodation and food and beverage, company services, and procurement of electricity and gas. The result of Klassen typology indicates that there are two superior sectors, those are agriculture, forestry and fishery, and procurement of electricity and gas which are in quadrant I position